Dasar, Aplikasi, dan Permasalahan Guru BK di Sekolah - Mutiara Putri Chandra; Neviyarni S.; Yarmis Syukur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the foundation, application, and problems of school guidance and counseling teachers using a descriptive qualitative approach. The results show that although guidance and counseling teachers have adequate theoretical and juridical understanding based on legal foundations such as Law Number 20 of 2003 and Minister of Education and Culture Regulation Number 111 of 2014, service implementation still faces various significant obstacles. Service applications include classical guidance, responsive services, and individual planning implemented through interactive methods and digital technology adaptation. The main problems identified include theory-practice gaps, negative stigma toward counseling services, excessive workload due to non-ideal teacher-student ratios (more than 150 students per teacher), educational background mismatch, minimal facilities and infrastructure, time limitations, suboptimal stakeholder collaboration, and adaptation challenges facing the complexity of digital era problems such as social media addiction and cyberbullying. Comprehensive solutions are needed in the form of continuous competency improvement, increasing the number of guidance and counseling teachers, clarification of main duties and functions, socialization of professional roles, and integration of digital technology in services to optimize student development and psychological well-being.